Preparing for a US Recession: Economic Implications and Policy Considerations - Angelov, Ivaylo (Journal of Environmental Science and Economics, 2023)
This study examines the potential US recession in 2023 and its economic implications, employing established economic models and indicators to assess the likelihood of a recession. By utilizing the Keynesian Cross and IS-LM models, we evaluate the effectiveness of policy responses and identify appropriate measures. The findings underscore the significance of timely and targeted stimulus, the need for coordinated monetary and fiscal policies, and the importance of long-term structural reforms. Based on these insights, policymakers are recommended to adopt proactive measures to mitigate the impact of the recession and promote economic stability.